ANALYSIS OF TRENDS IN ENSURING ECONOMIC STABILITY AND DEVELOPMENT OF INSURANCE COMPANIES IN THE REPUBLIC OF UZBEKISTAN (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the trends in ensuring the economic stability and development of insurance companies in the Republic of Uzbekistan. The study examines the modern features of insurance market development, including the implementation of digital technologies, the dynamics of financial indicators, and a rating-based analysis of leading insurance companies.